DEVELOPING RELIGIOUS MATURITY IN ADOLESCENTS: A STUDY OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN SCHOOLS - Rahmat, Munawar; Nurhuda, Abid; Putra, Farhan Akmala; Al Fajri, Muhammad; Huda, Ali Anhar Syi’bul (Universitas Tanjungpura, 2025)
This study aims to describe the religious maturity of adolescents with a survey of its review, namely school students so that the process, obstacles, and solutions for developing their religious maturity can be seen. The research design uses a qualitative approach with a literature review method with primary data in journals, books, papers, reports, and proceedings, and secondary data in the form of valid sources from the internet and documentation. After the data is collected, a descriptive and content analysis is carried out to obtain conclusions. The results of the study revealed that religious maturity in adolescence with a survey of its review, namely school students, occurs in three periods, early adolescence, middle adolescence, and late adolescence. In the early adolescent phase, there are doubts, hesitations, and confusion about beliefs in religious teachings and God, entering the middle phase, starting to search, and appreciate the values of religious teachings, and entering the final adolescent phase, their souls are increasingly stable. From the findings, it is known that the religious maturity of school students has not been optimal towards what is expected because, during monotonous religious learning, the problem of teacher competence is lacking, limited time, facilities, and the students themselves. Efforts that can be made are to develop a PAI curriculum, both in terms of design, methods, materials, media, and evaluations that are full of meaning, not justification, and provide opportunities and chances for students to internalize the values of religious teachings based on what they experience from real life.